Respostas
respondido por:
0
(80\x +1) - (x - 4) = 80
80 - (x+1)(x-4) = 80(x+1)
80 - (x² -4x + x - 4) = 80x + 80
-x² +3x + 4 - 80x = 80 -80
-x² - 77x + 4 = 0
-x² - 77x + 4 = 0
Δ = (-77)² - 4.(-1).4 = 5929 + 16 =5945
x' = (-83 + √5945)/2
x" = (-83 - √5945)/2
80 - (x+1)(x-4) = 80(x+1)
80 - (x² -4x + x - 4) = 80x + 80
-x² +3x + 4 - 80x = 80 -80
-x² - 77x + 4 = 0
-x² - 77x + 4 = 0
Δ = (-77)² - 4.(-1).4 = 5929 + 16 =5945
x' = (-83 + √5945)/2
x" = (-83 - √5945)/2
MALANCIA:
Não entendi a primeira parte da solução, por favor preciso entender como você encontrou 80 - (x + 1) (x - 4) = 80
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás